A Suprasegmental Feature of English Adjectives in “The Beauty and the Beast” - Ameer Yousif, Sinan; Mahdi Yousif, Salah; Salman Salih, Waleed (International Journal of Psychosocial Rehabilitation, 2020)
The study investigates syllable structure analysis of English adjectives in “The Beauty and the Beast.". The researchers construct the paper to include one unit. It discusses the notion of the syllable in English, types of a syllable, and the structure of the syllable. Also, it has a practical part, which in turn consists of methodology, data, findings, and conclusions. A tree diagram is used for the analysis of the syllables. For transcription, the Cambridge Advanced Dictionary is adopted. The researchers end up with the following concluding remarks: 1. The maximum syllable structure CCCVCCCC does not exist in the literary. The triggers are the writing style the dramatist has, which does not include complexity and sophistication. 2. The dominant syllable structure of monosyllabic adjectives that are taken from the literary work is CVC. This is part of the writing style that the dramatist follows, in which he seeks simplicity and clarity. However, it is the least frequent in disyllabic and polysyllabic adjectives. 3. The dominant syllable structure of disyllabic adjectives that are taken from the literary work is CV, while the least dominant syllable structures are CVCC, CCVC and V. Again, this is due to the style of the dramatist. 4. The dominant syllable structure of polysyllabic adjectives that are taken from the literary work is CVC, while the least dominant syllable structure is V. 5. The dramatist does not include in his work complicated adjective that include three or more syllables. On the contrary, the majority of the adjectives that he uses are monosyllabic.